Differential Impact of Combat on Postdeployment Symptoms in Female and Male Veterans of Iraq and Afghanistan. Issue 3 (1st March 2015) - Afari, Niloofar; Pittman, James; Floto, Elizabeth; Owen, Laura; Buttner, Melissa; Hossain, Nazia; Baker, Dewleen G.; Lindamer, Laurie; Lohr, James B.
ABSTRACT: Objectives: We aimed to describe differences in combat experience for male and female veterans and characterize differential effects on postdeployment physical and mental health symptoms, including aggression. Methods: Retrospective cross-sectional health screening data from 554 Operation Enduring Freedom and Operation Iraqi Freedom veterans who enrolled for Veterans Affairs health care in San Diego were examined including measures of combat experience, pain intensity, traumatic brain injury symptoms, military sexual trauma, post-traumatic stress disorder, depression, alcohol use, and aggression. Results: Although male veterans ( n = 458) experienced significantly higher rates of combat than female veterans ( n = 96), both experienced similar levels of postdeployment post-traumatic stress disorder and depression symptoms as well self-reported aggressive behavior compared to male veterans. Female veterans had higher rates of military sexual trauma and lower alcohol consumption than male veterans. Conclusions: All Operation Enduring Freedom and Operation Iraqi Freedom veterans returning from deployment may benefit from broad-based screening of physical and mental health symptoms, beyond those currently mandated by Veterans Affairs, including anger and aggression.